Reconsidering the “Critical-Corrective” Article of the Single Article Approved in September 2017 on “Iranian Citizenship of Children Born to Iranian Women Married to Non-Iranian Men” - Mostafa Daneshpajooh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The ambiguity and conciseness of the law on the citizenship of the children of Iranian mothers, on the one hand, and some dense social problems for the children of Iranian women married to Iraqi nationals and increasingly Afghan migrants, on the other hand, led the legislator to pass a single article in 2006. However, the conceptual ambiguities and implementation problems of this single article caused the legislator to repeal the previous single article by approving a new article in 1398.This article is an attempt to illustrate the article’s strengths and weaknesses by reconsidering the “critical-corrective” nature of the new single article, and especially to explain its incompatibility with the forty-first principle of the constitution; it is finally suggested that due to the truth and nature of citizenship and more compatibility with Article 41 of the Constitution, maternal lineage, like paternal lineage, secure the Iranian citizenship to the child.